Cross-sectional evaluation of patients with refractory or unexplained chronic cough by office-based pulmonologists in Germany - Peter Kardos; Heinrich Worth; Ulrich Koehler; Martin Horack; Barbara Karmann; Christina Jannowitz; Adrian Gillissen (Frontiers in Medicine)
BackgroundChronic cough (CC) is common in clinical practice, with refractory chronic cough (RCC) and unexplained chronic cough (UCC) being defined by guidelines from the European Respiratory Society, German Respiratory Society (DGP), and German Society of General Practice and Family Medicine (DEGAM) as separate entities. This study aimed to investigate the prevalence of RCC/UCC in an outpatient setting of pulmonologists.MethodsThis cross-sectional observational study was conducted in 16 pulmonologists’ offices in Germany. Adult patients with a specialist’s diagnosis of RCC or UCC and who provided informed consent were included. Active smokers were excluded.ResultsOf 22,140 consecutive out-patients screened, 421 were eligible for general analysis, and 226 met the RCC/UCC criteria per DGP guidelines for prevalence analysis. Among the 421 patients, 71.3% were female, 77.9% had therapy-resistant chronic cough (TRCC), and 22.1% had UCC. The main causes of TRCC were otherwise controlled asthma (59.1%) and gastroesophageal reflux disease (19.1%). Diagnosis had been established on average 6.4 ± 7.6 years prior. Common medications included inhaled corticosteroids (ICS/LABA: 45.6%, ICS mono: 26.8%), and herbal antitussives (23.3%). Codeine was used in 4.3% and morphine in 0.7%. Non-drug therapies like physiotherapy were infrequently used. Prevalence projections for RCC/UCC in Germany were 0.21 and 0.64%, based on different models.ConclusionThis study, the first in a secondary care setting in Germany to determine RCC/UCC prevalence in outpatients, found a higher prevalence in women and a long history of suffering. These findings underscore the need for improved diagnostic procedures and new therapeutic developments for RCC/UCC. Key limitations include the potential impact of the Covid-19 pandemic on data collection, a relatively small UCC sample, and potential referral bias due to the secondary care setting.